2013
DOI: 10.1080/10236244.2013.838028
|View full text |Cite
|
Sign up to set email alerts
|

One generation of inbreeding does not affect covering behavior of the sea urchinStrongylocentrotus intermedius

Abstract: To our knowledge, the genetic basis of covering behavior has never been investigated in sea urchins, although a number of hypotheses are well established to explain its potential significance since it was first documented more than 100 years ago. Whether there is a behavioral shift from juveniles to adults is also unknown in covering behavior. Here, we inbred sea urchins by one generation of full-and half-sibling inbreeding and then investigated the effects of inbreeding and age on covering behavior of Strongy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A big cluster of collector urchins is found in the Camarodonta, including collectors in the families of the Parechinidae, Strongylocentrotidae, Temnopleuridae and Toxopneustidae. We found one mention of an irregular echinoid (asymmetric sea urchins, sand dollars and their relatives) with covering behavior, the deep sea urchin Conolampas sigsbei, belonging to the family of the Echinolampadidae in the Neognathostomata branch of the irregularia (Zhao et al, 2013). We are aware that many irregularia bury themselves in the sediment.…”
Section: Echinoid Covering Behavior Evolutionmentioning
confidence: 98%
“…A big cluster of collector urchins is found in the Camarodonta, including collectors in the families of the Parechinidae, Strongylocentrotidae, Temnopleuridae and Toxopneustidae. We found one mention of an irregular echinoid (asymmetric sea urchins, sand dollars and their relatives) with covering behavior, the deep sea urchin Conolampas sigsbei, belonging to the family of the Echinolampadidae in the Neognathostomata branch of the irregularia (Zhao et al, 2013). We are aware that many irregularia bury themselves in the sediment.…”
Section: Echinoid Covering Behavior Evolutionmentioning
confidence: 98%
“…Inbreeding is the mating of related individuals, and it is practically unavoidable in captured populations because of restricted population sizes. Inbreeding can reduce the genetic variability of the population, resulting in the depression of key performance traits (Zhao, Feng, Tian, Zhou, Sun & Chang ). Although many studies have demonstrated that inbreeding can affect morphology (Luan, Yang, Wang, Luo, Chen, Gao, Hu & Kong ), hatchability (Moss, Arce, Otoshi & Moss ) and survival (Luo, Kong, Luan, Meng, Zhang & Wang ) in crustaceans, to our knowledge, no information is available on the effects of inbreeding on the physiological status, particularly the immune and antioxidant defence systems of crustaceans.…”
Section: Introductionmentioning
confidence: 99%
“…The reflexive hypothesis has been supported by several studies. One such study examined the covering behavior of Strongylocentrotus urchins and concluded that the reaction is innate because it is not affected by inbreeding or urchin age [8], suggesting that covering might not be decision based. It has also been noted that the stimuli often seemed to promote more activity in the animal [9].…”
Section: Introductionmentioning
confidence: 99%